Factors affecting supplier selection. A case study of The united nations - Mwangobole, Phillip (My University, 2011)
Procurement is one of the major functions in the peacekeeping missions and forms a central core in project implementation. The United Nations Budget is more than Five Billion United States dollars for projects in peacekeeping missions and post conflict zones. It has been noted that some goods are not delivered on time and with deviating specifications (poor quality not lasting long), within the contractual framework that has been signed by between the United Nations and the Supplier. There is a need to examine how the different vendors are selected and how their selection has an implication on the performance. This means measuring output in terms of time and quality of work as per laid down standards. The objectives of this study are to determine the factors that affect supplier selection at the United Nations. Main emphases arc on finding out the effects of pricing, supplier experience, quality and financial capacity of suppliers on supplier selection. The study adopted descriptive design to determine the factors that affect effective supplier selection at the United Nations. The target population was United Nation procurement management teams while the main research instrument that was used in data collection is a semi-structured self administered questionnaire. The sample frame for the study comprised a group of 94 employees from the UN while the sample of the study includes 57 employees of the same organization chosen from specific departments that greatly take responsibility in procurement processes through simple random sampling. A qualitative and quantitative analysis was used to analyze the findings of the study (though qualitative analysis was used in great amounts due to the design of questions). Data was analyzed using excel spreadsheets. The finding of the study reveals that pricing of the products, supplier’s experience, quality of the products, and financial capacity has great influence on supplier’s selection particularly in United Nations. The study recommended that a study should be conducted to look at the factors affecting supplier selection in an e-procurement system. This is because growth in business-to-business e-commerce remains strong as information and communications technologies (ICTs) continue to transform organizations’ interactions with their suppliers and customers (Mullaney, 2003; European Commission, 2005a).